Properties of sulphur in colloidal system: a review - Omar, Mohamad Firdaus; Mohamad, Nuriah; Azmi, Azlin Suhaida; Ali, Fathilah (Kulliyah of Engineering, International Islamic University Malaysia (IIUM), 2019)
Sulfur has been highly sought by many industries everywhere around the world for various applications. This exceptionally useful element has been largely manufactured especially in powder form each year reflecting its increase in demand in line with technological advancement and uses for various product applications. The manufacturing processes include mining as well as chemical reactions in Claus Process. Rubber industries normally use abundance of sulfur in their latex compound to introduce vulcanization. The geneal concern of sulfur for rubber vulcanization is dispersibility in the rubber matrix due to improper optimization of its preparation process prior to latex compounding. Another crucial issue is crystallization of soluble sulfur from its insoluble origin, either during or post-rubber vulcanization that constitutes to formation of sulfur bloom that grows on the surface of the rubber articles. It is known that both issues are related to the process conditions and compounding recipe that could not be fully solved. Various studies have been conducted to minimize such occurences – from process optimization to sulfur chemistry itself – and of continuous improvement and innovation to solve various threats in sulfur applications. This paper reviews on detailed description on elemental sulfur, of respective industrial applications, and most importantly highlights on sulfur trends and issues normally encountered.